STUDI TENTANG BENTUK, MOTIF DAN MAKNA TANJAK PADA MASYARAKAT MELAYU DI KABUPATEN SIAK PROVINSI RIAU - FENY SANTIA, Dra. Zubaidah, M.Pd., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2018)
The research of this study were (1) to describe the shape of tanjak in the Malay community in Siak Regency, Riau Province, (2) to describe the tanjak motive in the Malay community in Siak Regency, Riau Province Research, (3) to describe the mean of tanjak in the Malay community in Siak Regency, Riau Province. This research was conducted in Siak Regency, Riau Province. This type of research is qualitative research with descriptive methods. Data collection in this study is observation, interviews and documentation. The conclusions of the study are: found two forms of tanjak, namely fauna and geometric. the form of fauna is found on tanjak elang menyongsong angin, pial ayam, elang patah kepak and pari mudik. while the geometric shape is found on tanjak dendam tak sudah. The motives found are four kinds, namely: pucuk rebung motifs, Tampuk manggis motifs, itik tidur motifs and wajik motifs. The meaning of tanjak dendam tak sudah: Tanjak dendam tak sudah not have the meaning of love, tanjak Elang menyongsong angin symbolizes wisdom and precision, tanjak pial ayam has the meaning of courage, tanjak Elang patah kepak and has a sense of responsibility, Tanjak pari mudik means having humility and harmony.Keywords: Tanjak, shape, motive, meaning